The Role of Neglect in Child Fatality and Serious Injury. (July 2014) - Brandon, Marian; Bailey, Sue; Belderson, Pippa; Larsson, Birgit; Appleton, Jane V.; Sidebotham, Peter
<x xml:space="preserve">Abstract</x> Although there is improved recognition of the pernicious long‐term harm that stems from living with neglect during childhood, neglect is rarely associated with child fatality. This article offers a re‐analysis of neglect in serious case reviews (cases of child death or serious injury related to maltreatment) in England (2003–11) from four consecutive government‐commissioned national two‐yearly studies. It draws on anonymised research information from 46 cases out of a total of over 800 cases. Each case was examined in depth using an ecological transactional approach, grounded in the child's experience, which promotes a dynamic understanding and assessment of the interactions between children and their families and the helping practitioners. The qualitative findings reported explore how circumstances came together when neglect had a catastrophic impact on the child and family presenting in six different ways (deprivational neglect, medical neglect, accidents with elements of forewarning, sudden unexpected deaths in infancy, physical abuse combined with neglect and young suicide). Each of the six categories raised particular issues over and above a common core of concerns around the relationship between the child and his or her parent or carer, and between parents/carers and professionals. © 2014 The Authors. Child Abuse Review published by John Wiley & Sons Ltd. <boxed-text content-type="pullQuote" id="car2320-blk-0001" position="anchor" orientation="portrait"> 'neglect is rarely associated with child fatality' </boxed-text> <boxed-text content-type="pullQuote" id="car2320-blk-0002" position="anchor" orientation="portrait"> 'Each of the six categories raised particular issues' </boxed-text> Key Practitioner Messages: There are no easy answers to curbing potentially fatal neglect – practitioners should be supported to make careful well‐reasoned judgements. That neglect is not only harmful but can also be fatal should be part of any practitioner's mindset, as with other maltreatment. To guard against catastrophic neglect, children need to be physically and emotionally healthy and have a safe, healthy living environment. Practitioners need to be compassionate and sensitively attuned to the relationship between parents and children. <boxed-text content-type="pullQuote" id="car2320-blk-0031" position="anchor" orientation="portrait"> 'practitioners need to be compassionate and sensitively attuned to the relationship between parents and children.' </boxed-text>